STANDARD OF PRMS-SPE: METHODICAL ASPECTS, RESULTING ACCOUNTING AND POSSIBILITY OF APPLICATION TO GEE OF OIL AND GAS SUPPLIES IN UKRAINE - Rudko, G.; Mykhailiv, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article gives detailed description of PRMS-SPE, as one of the leading international systems for the evaluation of hydrocarbons supplies and resources. Their category and classes are distinguished by the degree of beds studying, expected economic effects from their exploitation and state of present wells. The calculation of gas deposit supplies after the criteria of PRMS – SPE was carried out. The comparison of the results that was conducted with the requirements of minerals supplies and resources Classification of the earth crust state fund was made. This Classification defined methodical principles of calculation, recording, and control of minerals inventories in Ukraine. The calculated volumes of hydrocarbons in the certain measure comparable in general size, howeve, are redistributed in different groups and categories. Reporting on supplies/resources of these two standards cardinally differs, that is determined by differences in approach to the selection of categories and establishment of bordersunder which the calculation of supplies is conducted.